Implementation of a methodology to quantify microcirculatory parameters in cerebral tissue of a swine model in vivo (2012)
Maintenance of the microcirculatory function has been proposed as a key factor for the positive outcome of the performance of artificial oxygen carriers and plasma expanders. Such products are used to restore blood volume and oxygen carrying capacity in cases of hemorrhagic shock. The majority of the experimental data in which all this theory is based was obtained from a skin fold window chamber preparation that allows the direct visualization of the muscle and connective tissue microvessels. This vessels are thought to be the first tissues to be shot down during severe bleeding due to control mechanisms. For this reason the visualization and measurements should be done in the microcirculation of the main organs whose survival is highly compromised during hypoxia such as the brain, to contrast with the existing data. In this document a summary of a year of work for the implementation of a methodology for the direct visualization and quantification of microcirculatory parameters in cerebral tissue of a swine model is presented.